Searching for sterility genes in bulb onion breeding accessions with the use of DNA markers - Artur S. Domblides (Овощи России, 2019)
Relevance. Sterility is a very important trait that is indispensable for hybrid production. Genetic factor underlying in plant sterility can be now identified in large plant populations by DNA markers with high effectiveness and reliability. The evaluation of such markers enables to define their current applicability in breeding program.Methods. The markers from different publications that had been successfully used were taken to test their effectiveness on 19 accessions of bulb onion (Allium cepa L.).Results. Mitochondrial genes 5’cob, orf725 and orfA501 and alleles of fertility restoring locus Ms were also identified. Four breeding accessions had S-cytoplasm, nine accessions were with T-cytoplasm and six shared normal cytoplasm not showing any sterility gene in the analysis. As a result of marker testing, the all compositions of the genes in cytoplasm and Ms alleles in nucleus affecting the sterility had been revealed, such as one sterility maintainer, one male sterile accession, and two fertility restorers. However, it should be noted that not all markers tested were in accordance with each other, where the markers originated from chloroplast DNA of did not confirmed the results obtained with those cytoplasm-origins. As it was shown the practical use of the set of markers makes it possible to reveal necessary accessions with required gene composition for hybrid production in bulb onion.